35.2k views
3 votes
What is the solution to the equation 3x + 2(x − 9) = 8x + x + 2? (1 point)

−16
−5
5
16

2 Answers

2 votes

Answer:

x = -5

Explanation:

3x + 2(x - 9) = 8x + x + 2

-----Distribute left side-----

3x + 2x - 18 = 8x + x + 2

-----Combine like terms-----

5x - 18 = 9x + 2

-----Add 18 to both sides-----

5x = 9x + 20

-----Subtract 9x to both sides-----

-4x = 20

-----Divide -4 to both sides-----

x = -5 <---

Good luck on your exam! :D

User Mohammad Ashfaq
by
5.0k points
1 vote

Answer:

x = -5

Explanation:

3x + 2(x - 9) = 8x + x + 2

~Distribute left side

3x + 2x - 18 = 8x + x + 2

~Combine like terms

5x - 18 = 9x + 2

~Add 18 to both sides

5x = 9x + 20

~Subtract 9x to both sides

-4x = 20

~Divide -4 to both sides

x = -5

Best of Luck!

User Clouddy
by
4.7k points